Peningkatan Produktivitas Dan Kinerja Lingkungan Menggunakan Metode Green Productivity - Hersandi Hamdan Pratama (Jurnal Teknik Industri, 2015)
Every company certainly wants to increase their productivity, such as by increasing the amount of production. However, as goes by production, important to notice the aspects surrounding of the environment performance. Therefore we need a method to improve productivity and environmental performance simultaneously. The purpose of this study is to identify factors that affect the productivity and environmental performance, and provide suggestions using the method of Green Productivity improvements based on the highest value of Green Productivity Index. Based on research in PG Kebon Agung there are two alternative solutions that improve productivity and environmental performance, but the GPI of alternative 2 is bigger than ternative 1 which is 4,47. The alternative is additional outlet capacity at waste treatment plants. This solution provides increased productivity, where the initial productivity of 136.045% to 136.05%. With the implementation of alternative solutions can improve EPI index up 0.32 so to give an increase in the Index EPI (Environmental Performance Indicator) from 0.46 became 0.78